Pendampingan Microsoft Office Bagi Peserta Didik Kelas Menengah Kampung Babakan Anyar Desa Jatimulya - Fian Firmansyah; Devaron Suardi; Rihatul Jannah; Ira Asyura (Universitas Teuku Umar, 2023)
Capabilities and skills in using Microsoft Office become very important in the pandemic era and digital era with high technology. It becomes the main medium in online learning and the main support in the face-to-face or direct learning process. However, in some areas, especially rural areas, there are still schools with limited facilities and infrastructure in providing facilities in the implementation of learning facilities, so that using technology such as computers cannot be applied optimally in schools. Thus the learning process is only one way and will reduce the level of creativity of students in learning and teaching process. Thus, the ability of students in operating microsoft office is still lacking and assistance is needed as a support for students in operating microsoft office, especially during this pandemic. This devotional activity was carried out in September 2021 in Babakan Anyar, Jatimulya village. This activity is divided into planning and implementation activities. Microsoft Ofiice mentoring activities that include Ms. Word, Ms. Excel, Ms. Power Point make students understand how to use Microsoft office, so that students can apply knowledge during the learning process and when doing schoolwork.